ANALYSIS OF TWO FLUORESCENT MOLECULES PROPERTIES USING SOLVATOCHROMIC SHIFT METHOD: Life Science-Physics - N.R. PATIL; R. M. MELAVANKI; B. M. CHOUGALA; L.A. SHASTRI; F M SANNINGANNAVAR (International Journal of Life Science and Pharma Research, 2012)
The absorption and emission spectra of two fluorescent coumarins molecules coumarins namely 5BAMC and 4DHMC have been recorded at room temperature in solvents of different polarities. The ground state dipole moments (g) of two coumarins were determined experimentally by Guggenheim method. The exited state (e) dipole moments were estimated from Lippert’s, Bakhshiev’s and KawskiChamma-Viallet’s equations using the variation of Stoke’s shift with the solvent dielectric constant and refractive index. The geometry of the molecule was fully optimized and the g were also calculated theoretically by Gaussian 03 software using B3LYP/6-31g* level of theory. Further, Δµ were calculated both from solvatochromic shift method on the basis of microscopic solvent polarity parameter ( ) and the values are compared. The g and e were calculated by means of solvatochromic shift method and e was determined in combination with g. It was observed that e were higher than those of the g, indicating a substantial redistribution of the π-electron densities in a more polar excited state for two coumarins.